P599 Short- and long-term outcome of minimally invasive approach for Crohn's disease: Comparison between single incision, robotic-assisted and conventional laparoscopy. (16th January 2018) - Zambonin, D; Giudici, F; Ficari, F; Rogai, F; Scaringi, S
Abstract: Background: The feasibility of the minimally invasive approach for Crohn's disease (CD) is still controversial. Several meta-analysis and retrospective studies demonstrated the safety and benefits of laparoscopy for CD patients. Laparoscopic surgery can also be considered for complex disease and recurrent disease.16 The aim of this study was to investigate retrospectively the effect of three minimally invasive techniques on short- and long-term postoperative outcome. Methods: We analysed CD patients underwent minimally invasive surgery in the Digestive Surgery Unit at Careggi University Hospital (from January 2012 to march 2017). Short-term outcome was evaluated on Dindo Clavien classification and postoperative pain. Long-term outcome was evaluated on 4 questionnaires: Short Form Health Survey (SF-36), Gastrointestinal Quality of Life Index (GIQLI), Body Image (BIQ), Hospital Experience (HEQ). Results: There are 89 patients: 63 conventional (CVL), 16 single incision (SILS) and 10 robotic assisted (RALS) laparoscopy. Albuminemia <30 g/l ( p = 0.031) resulted to be a risk factor for postoperative complications. HEQ had a better result for RALS ( p = 0.019), while no differences resulted for SF36, BIQ and GIQLI. Conclusions: Minimally invasive technique for CD is feasible, even for complicated and recurrent disease. Our study demonstrated low rates of short- and long-term postoperative complications. No difference between techniques were demonstrated. Further studies, with a larger and sample size and randomised controlled design, should be performed to assess the best surgical technique.